2018
DOI: 10.1101/362004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decreased IgG core fucosylation, a player in antibody-dependent cell-mediated cytotoxicity, is associated with autoimmune thyroid diseases

Abstract: Martin et al., Decreased IgG core fucosylation, a player in antibody-dependent cellmediated cytotoxicity, is associated with autoimmune thyroid diseases, 2018 (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. • Polish cohort: The study was supported by the grants from the Jagiellonian University (PBMC glycosylation, K/DSC/001749; IgG glycosylation, K/DSC/002341).• IgG glycan analysis in the three cohorts was performed in Genos Glycoscie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 72 publications
1
29
0
3
Order By: Relevance
“…2a) . It is noteworthy that we previously showed that there are negative correlations between the set of IgG N-glycan traits without core fucose (IGP2, IGP42, IGP46) and the set of IgG N-glycan traits describing IgG core fucose (IGP58, IGP59, and IGP60) 4 and these are highlighted in Fig. 2b .…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…2a) . It is noteworthy that we previously showed that there are negative correlations between the set of IgG N-glycan traits without core fucose (IGP2, IGP42, IGP46) and the set of IgG N-glycan traits describing IgG core fucose (IGP58, IGP59, and IGP60) 4 and these are highlighted in Fig. 2b .…”
Section: Resultsmentioning
confidence: 62%
“…a) Heatmap of immune cell traits associated with AITD-IgG N-glycan traits. The 51 NK cell types were significantly associated with 6 out of 17 AITD-IgG N-glycan traits previously identified 4 . Below the heatmap, there are one representative of IgG core afucose (IGP2) and one representative of IgG core fucose (IGP7), that were both associated with AITD and TPOAb levels 4 .…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations